The reality of applying total quality management at the University of Idlib from the point of view of faculty and administrative academics - Staif, Ahmad Mohamad; Abdulaziz, Siham Mustafa; Abd Alsid, Hisham Farag (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of application of total quality management with its following dimensions (organizational culture, academic field, professional growth) from the point of view of faculty members and administrative academics at the University of Idlib. To achieve the goal of the study, the researcher used the descriptive analytical method, and the study tool was a questionnaire composed of (24) items distributed on three axes: Organizational culture (8) items, academic field (6) items, professional growth (10) items, applied to a sample of (82) faculty members at the University of Idlib. The study found that the degree of application of comprehensive quality management in its following dimensions: (organizational culture, academic field, professional growth) at the University of Idlib from the point of view of faculty and administrative academics was moderate on the three principles with an average calculation ranging from (2.92 - 3.43) to an average application degree. The first was the academic field with an average calculation (3.43), second after professional growth and average calculation (3.09), and third after organizational culture with an average calculation (2.92). The study also found that there are no statistically significant differences in the level of indication (α≤ 0.05) in the degree of application of CQM in the following dimensions: (organizational culture, academic field, professional growth) at the University of Idlib from the point of view of the faculty and administrative academics of the University of Idlib attributable to the variables of scientific qualification (master’s, Ph.D.), as well as the absence of statistically significant differences at the indicative level (α≤ 0.05) attributable to the job title variable (faculty member, administrative academic). The study concluded that the idea of working in a team spirit and involving everyone in decision-making should be strengthened, and that the University should be interested in developing its libraries, research that would be able to meet the requirements of its students and faculty.